AgNPs Aggravated Hepatic Steatosis, Inflammation, Oxidative Stress, and Epigenetic Changes in Mice With NAFLD Induced by HFD - Wen, Ling; Li, Minyan; Lin, Xiaojun; Li, Yan; Song, Huidong; Chen, Hanqing (Frontiers in Bioengineering and Biotechnology, 2022)
The recent development of silver nanoparticles (AgNPs) has sparked increased interest in biomedical and pharmaceutical applications, leading to the possibility of human exposure. The liver is the primary target organ in the metabolism and transport of nanoparticles. Nonalcoholic fatty liver disease (NAFLD) is the most common and leading cause of hepatic metabolic syndrome with approximately 15% of patients will develop into nonalcoholic steatohepatitis, fibrosis, cirrhosis, and eventually hepatocellular carcinoma. Thus, the potential hepatotoxicity of AgNPs on NAFLD development and progression should be of great concern. Herein, we explored the potential hepatic effect of a single intravenously injected dose of 0.5, 2.5, and 12.5 mg/kg BW on the liver function of high-fat-diet (HFD)-fed mice for 7 days. AgNP treatment increased serum levels of alanine aminotransferase, aspartate transaminase, triglycerides and cholesterols, the number of lipid droplets, and the contents of triglycerides and cholesterols in NAFLD mice livers compared to HFD-fed mice. The mechanism of AgNP-induced worsen hepatotoxicity in mice is associated with hyperactivation of SREBP-1c-mediated de novo lipogenesis and liver inflammation. Additionally, HFD-fed mice treated with AgNPs had significantly higher oxidative damage and lower global DNA methylation and DNA hydroxymethylation than NAFLD mice. This study suggests that AgNP treatment exacerbated HFD-induced hepatic steatosis, liver inflammation, oxidative stress, and epigenetic changes in mice, which is relevant to the risk of AgNP exposure on NAFLD development and progression.